DIAGNOSA KERUSAKAN MESIN TIPE OM366A PADA MOBIL MERCEDES-BENZ MENGGUNAKAN SISTEM PAKAR - Rizal Rizal (TECHSI - Jurnal Teknik Informatika, 2013)
An expert system is a transfer of knowledge from an expert to a computer system, so the  system can be used by people who are not experts in solving the problem as was done by experts. Many cases can be used as research in expert systems, one of which diagnoses the cause engine damage. This research will design an expert system that can diagnose the cause of damage to the engine type OM366A ercedes-Benz. The method used in this study is the use of backward chaining method in the process of diagnosing it. This expert system is very useful to make it easier for technicians to perform diagnostics, so that will speed in getting a solution to the cause engine damage and repair actions in accordance with the selected type of damage and without the presence of an expert. This expert system application designed using Microsoft Visual Basic.Net 2008, Add-On Develover Express 2011and Microsoft Access 2010 as a repository for the knowledge base.